Iron complex catalyzed selective C-H bond oxidation with broad substrate scope - Jana, Sandipan; Ghosh, Munmun; Ambule, Mayur; Sen Gupta, Sayam (Organic Letters, 2017)
The use of a peroxidase-mimicking Fe complex has been reported on the basis of the biuret-modified TAML macrocyclic ligand 'framework (Fe-bTAML) as a catalyst to perform selective oxidation of unactivated 3 degrees C-H bonds and activated 2 degrees C-H bonds with low catalyst loading (1 mol %) and high product yield (excellent mass balance) under near neutral conditions and broad substrate scope (18 substrates which includes arenes, heteroaromatics, and polar functional groups). Aliphatic C-H oxidation of 3 and 2 sites of complex substrates was achieved with predictable selectivity using steric, electronic, and stereoelectronic rules that govern site selectivity, which included oxidation of (+)-artemisinin to (+)-10 beta-hydroxyartemisinin. Mechanistic studies indicate Fe-V(O) to be the active oxidant during these reactions.